2005
DOI: 10.1158/1078-0432.ccr-04-1951
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Mevalonate Pathway Inhibits the Function of the Epidermal Growth Factor Receptor

Abstract: Purpose: The epidermal growth factor receptor (EGFR) is a key regulator of growth, differentiation, and survival of epithelial cancers. In a small subset of tumors, the presence of activating mutations within the ATP binding site confers increased susceptibility to gefitinib, a potent tyrosine kinase inhibitor of EGFR. Agents that can inhibit EGFR function through different mechanisms may enhance gefitinib activity in patients lacking these mutations. Mevalonate metabolites play significant roles in the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 30 publications
6
103
1
3
Order By: Relevance
“…Using EGFR-targeting agents requires combination-based therapies to enhance their clinical activity. Our recent studies have shown that the depletion of mevalonate metabolites affects the activity of a number of cell signaling cascades, including inhibitory effects on EGFR activity and their downstream signaling pathways (Mantha et al, 2005;Niknejad et al, 2007). Combinations of statins with agents targeting EGFR activity, such as gefitinib, induce a potent synergistic cytotoxic response in a variety of responsive tumor types, including SCC (Mantha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using EGFR-targeting agents requires combination-based therapies to enhance their clinical activity. Our recent studies have shown that the depletion of mevalonate metabolites affects the activity of a number of cell signaling cascades, including inhibitory effects on EGFR activity and their downstream signaling pathways (Mantha et al, 2005;Niknejad et al, 2007). Combinations of statins with agents targeting EGFR activity, such as gefitinib, induce a potent synergistic cytotoxic response in a variety of responsive tumor types, including SCC (Mantha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have shown that the depletion of mevalonate metabolites affects the activity of a number of cell signaling cascades, including inhibitory effects on EGFR activity and their downstream signaling pathways (Mantha et al, 2005;Niknejad et al, 2007). Combinations of statins with agents targeting EGFR activity, such as gefitinib, induce a potent synergistic cytotoxic response in a variety of responsive tumor types, including SCC (Mantha et al, 2005). Combining these two approaches, with each targeting the EGFR through distinct mechanisms, represents a novel combinational therapeutic approach in SCC, as well as in other cancers in which EGFR is involved in their pathogenesis (Dimitroulakos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…trastuzumab, gefitinib) resultaría en una mayor respuesta terapéutica por parte de algunos cánceres (ej. tumores gastrointestinales, mama, pulmón) [38][39][40] . Los autores, tal como muestra la Figura 4, han demostrado la Inhibición de invasión y metástasis inhibición de rho ↓expresión de metaloproteinasas de la matriz (MMP-9)…”
Section: C) Efectos De La Asociación De Estatinas a Terapias Actualmeunclassified